Implementasi Akad Ijarah pada Persewaan Perlengkapan Bayi Baby Farra Rental Surabaya - Tiara Dhea Octavianti (Journal of Islamic Economics and Finance Studies, 2020)
Fiqh muamalah is a rule or procedure that can be used as a guide for humans to communicate with each other through cooperation using Islamic legal guidelines. One of them is the Ijarah method or lease. Meeting the needs of babies is one of the top priorities in the family. One of them is fulfilling the needs of baby equipment which aims to make it easier for parents to care for their children. Besides that, it is also for comfort and helps the development of children. However, the high price and the limited use period along with the development of the baby are the factors inhibiting the fulfillment of these needs. One way to meet these needs is by renting. The baby equipment rental business is one of the most open business opportunities and is needed by the community. One of these business actors is the Baby Farra Rental baby equipment rental. Although the rental system carried out at Baby Farra rental still uses conventional methods. Business owners, employees and consumers of Baby Farra Rental also do not know about what the Ijarah Agreement is, but in the implementation of the lease it is in accordance with the principles and conditions of the ijarah including starting from Aqil or the person who leases the lease, sighat contract or consent qabul, ujroh or fee rent and the benefits of the ijarah itself. The existence of a baby equipment rental business is very beneficial financially for the community, especially families who have babies who have economic limitations.